Training and assistance in clean water treatment for communities to meet hygienic water needs - Bambang Suhartawan; Suyatno Suyatno; Alfred Benjamin Alfons; Andrea Karina Marielle P. Abel; Katherina T. J. Mayor Sroyer (University of Merdeka Malang, 2025)
Yobeh Village, located in the Sentani district, consisted of 3 community units (RW) and 7 neighborhood units (RT) with a total of 173 families and 692 residents. A portion of the community, approximately 56 families with around 246 residents, lived along the shores of the island in the Lake Sentani area. The waters of Lake Sentani served as the